An Engineered Intravitreal Injection Retinal-Pigment-Epithelium-Tropic Adeno-Associated Virus Vector Expressing a Bispecific Antibody Binding VEGF-A and ANG-2 Rescues Neovascular Age-Related Macular Degeneration in Animal Models and Patients - Yuan Cai; Yonghao Gu; Jie Zhang; Ying Zhu; Zhen Ma; Qin He; Yongjia Sun; Mengmeng Yuan; Xiaojun Li; Kai Zhu; Bolong Miao; Jin Zhao; et al. (Research)
Antiangiogenesis gene therapy based on adeno-associated virus (AAV) vectors represents a promising advancement in the treatment of neovascular age-related macular degeneration (nAMD), providing an alternative to antibody-based therapies. However, the development of a safe and effective AAV vector capable of precisely targeting neovascularization and choroidal leakage remains a critical unmet need. In the present study, we engineered a novel intravitreally administered AAV vector with retinal-pigment-epithelium (RPE)-specific tropism. This vector demonstrated robust and localized gene expression in RPE cells while maintaining a favorable safety profile. The RPE-tropic AAV vector delivered a dual-acting antibody against vascular endothelial growth factor (VEGF) and angiopoietin-2 (ANG-2), exhibiting strong therapeutic efficacy and tolerability in both rodent and nonhuman primate choroidal neovascularization models. Based on the promising preclinical data, a single-center, single-arm, investigator-initiated trial (ChiCTR2400085329) was conducted to assess its safety and efficacy in patients with nAMD. The RPE-tropic AAV vector expressing anti-VEGF-A and anti-ANG-2 effectively alleviated disease progression and was well tolerated in the clinical setting. These findings highlight the potential of this engineered AAV-RPE capsid as a versatile platform for gene therapy, not only for nAMD but also for other ocular diseases involving RPE cells.